Collaborative Multi-Robot Transportation in Obstacle-Cluttered Environments via Implicit Communication - Bechlioulis, Charalampos P.; Kyriakopoulos, Kostas J. (Frontiers in Robotics and AI, 2018)
This paper addresses the problem of cooperative object transportation in a constrained workspace involving static obstacles, with the coordination relying \textcolor{blue}{on implicit communication established via the commonly grasped object}. In particular, we consider a decentralized leader-follower architecture for multiple mobile manipulators, where the leading robot, which has exclusive knowledge of both the object's desired configuration and the position of the obstacles in the workspace, \textcolor{blue}{tries to navigate the overall formation to the desired configuration while at the same time it avoids collisions with the obstacles}. On the other hand, the followers estimate the object's desired trajectory profile via novel prescribed performance estimation laws that drive the estimation errors to an arbitrarily small predefined residual set. \textcolor{blue}{Moreover, a navigation function-based scheme is innovatively combined with adaptive control to deal with parametric uncertainty. Hence, the current state of the art in robust motion planning and collision avoidance is extended by studying second order nonlinear dynamics with parametric uncertainty.} Furthermore, the feedback relies exclusively on each robot's force/torque, position as well as velocity measurements and no explicit information is exchanged online among the robots, thus reducing the required communication bandwidth and increasing robustness. Finally, two simulation studies clarify the proposed methodology and verify its efficiency.